2019
DOI: 10.1039/c8ay02152j
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria-targetable colorimetric and far-red fluorescent probe for the sensitive detection of carbon monoxide in living cells

Abstract: A simple colorimetric and far-red fluorescent probe was developed for the first time to visualize the gasotransmitter carbon monoxide in subcellular mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Fluorescent sensors utilize the photoluminescence response triggered by reaction between CO and fluorescent probes for CO measurements in living tissues and aqueous solutions [ 32 , 72 , 73 ]. The transition metal complexes employed in some CO colorimetric, such as ruthenium, iridium, and rhenium, can also be used for fluorescent CO detection [ 56 , 68 , 74 ].…”
Section: Dissolved Co Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent sensors utilize the photoluminescence response triggered by reaction between CO and fluorescent probes for CO measurements in living tissues and aqueous solutions [ 32 , 72 , 73 ]. The transition metal complexes employed in some CO colorimetric, such as ruthenium, iridium, and rhenium, can also be used for fluorescent CO detection [ 56 , 68 , 74 ].…”
Section: Dissolved Co Measurement Methodsmentioning
confidence: 99%
“…The review suggests that direct measurement of DCO concentration might be achieved using colorimetric sensors fabricated with transition metal complexes, fluorescent sensors with transition metal complexes, fluorescent proteins, or palladium catalyzed Tsuji–Trost reaction. However, the drawbacks of colorimetric sensors and fluorescent sensors in the reversibility issue, such as a long recovery time [ 70 ], reagents [ 73 ], and heating [ 84 ] aided reversibility, indicate that these sensors are most appropriate for offline, disposable DCO measurement.…”
Section: Dissolved Co Measurement Methodsmentioning
confidence: 99%
“…colourless to pink in aqueous solution makes it suitable for visual detection of CO. Fluctuation of CO levels in living cells also provide an avenue to make it suitable to understand the biological functioning of mitochondrial CO in living HeLa cells. [68] Zhou et al reported a new rhodamine centred mitochondria targetable specific CO detection probe RCO having a reactionbased opening of the spirolactam ring without using Pd 2 + which is distinct in literature. Due to the high allergic and toxic effect Pd 2 + mediated detection of CO is supposed to be less favourable than the palladium free reaction-based detection which is inexpensive as well.…”
Section: Fluorescent Probes For Mitochondrial-targetable Co Detectionmentioning
confidence: 99%
“…reported a far‐red probe FR‐CO for the detection of CO levels in mitochondria of living cells (Figure ). The colorimetric detection of CO by changing colour from colourless to pink in aqueous solution makes it suitable for visual detection of CO. Fluctuation of CO levels in living cells also provide an avenue to make it suitable to understand the biological functioning of mitochondrial CO in living HeLa cells …”
Section: Fluorescent Probes For Mitochondrial‐targetable Co Detectionmentioning
confidence: 99%
“…Each detection method has its own unique advantages and has been widely used. With the continuous development of science and technology, among these methods colorimetric fluorescence probes have been given much attention by researchers because they can not only detect analytes by the naked eye, but also have advantages of rapid response, high sensitivity, and selectivity . Among the synthesized and reported fluorescent probes for the detection of NO 2 − , aromatic ortho‐diamines are usually used as probes, and are able to react with NO 2 − to yield benzotriazole derivatives in an acidic medium.…”
Section: Introductionmentioning
confidence: 99%